A new entity in the pathological spectrum of vulvar neoplasms: The first report of a primary endometrioid adenocarcinoma. Issue 2 (20th August 2019) - Inzani, Frediano; Angelico, Giuseppe; Santoro, Angela; Musarra, Teresa; Valente, Michele; Spadola, Saveria; Garganese, Giorgia; Fragomeni, Simona; Scambia, Giovanni; Zannoni, Gian Franco
Abstract : We report the first evidence of primary endometrioid adenocarcinoma arising in the vulva, expanding the morphological spectrum of the glandular neoplasms in this anatomic region.